Effect of dietary incorporation of Spirulina platensis on the growth performance, carcass characteristics and meat quality in broilers - Venkateswarlu, S; Devasena , B; Sudheer , K (Journal of Meat Science, 2024)
This study was conducted to evaluate the effect of Spirulina platensis on growth performance, physiochemical properties of meat, carcass characteristics and breast meat quality in broilers. A total of 144-day old commercial broiler chicks were randomly divided into 3 dietary treatments with 4 replicates having 12 birds per replicate for a period 6 weeks. The dietary treatments were 0 (T1), 1(T2) and 2(T3) % spirulina inclusion in rations. Significantly (P<0.01) higher body weight gain, feed intake and better feed conversion ratio was observed in 1% spirulina supplemented groups. The meat quality parameters viz., crude protein, redness (a*) and yellowness (b*) were significantly (P<0.05) higher in 1% spirulina supplemented groups compared to control. However, no significant difference was observed between spirulina fed groups. Microbial analysis indicates that total plate count (TPC), psychrophiles, yeast and moulds in meat was decreased (P<0.05) linearly as the level of spirulina increased from 0 to 2 %. Sensory attributes like tenderness, juiciness and overall acceptability were significantly (P<0.05) higher in spirulina supplemented groups. Carcass traits revealed that significantly (P<0.05) higher skin weight was observed in control compared to other treatments. However, no significant difference in other parameters like carcass weight, breast weight and carcass percentage. The results indicates that supplementation of spirulina in broiler diets improved the growth performance, increased meat colour, quality and overall acceptability. Hence, it can be concluded that spirulina powder can be fed up to 1 per cent level to improve the broiler production.